FACTORS ASSOCIATED WITH NEONATAL OUTCOMES IN PREMATURE RUPTURE OF MEMBRANES - Irmayani, Putri; Cut Meurah Yeni; Rena Meutia (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Premature rupture of membranes (PROM) increases the risk of maternal infection and neonatal morbidity. A cross-sectional study at Pertamedika Ummi Rosnati Hospital (July–October 2025) involved 31 pregnant women with PROM. Data included maternal age, leukocyte count, birth weight, gestational age, and infant outcomes (NICU vs. rooming-in). The mean maternal age was 29.5 years, birth weight 2682 g, and leukocyte count 13.3 thousand/μL. Infant birth weight differed significantly between the NICU (2300 g) and rooming-in (2839 g) groups (p=0.001). Preterm gestational age was associated with NICU admission (p=0.003), with 66.7% of preterm infants requiring NICU admission. Birth weight was strongly correlated with Apgar score (r=0.599; p<0.001), while maternal age and leukocyte count were not significant. Analysis indicates that birth weight and gestational age are the main factors in neonatal outcomes in PROM. Close monitoring and clinical management are needed to improve outcomes.